Enzymatic assembly of DNA molecules up to several hundred kilobases. - Gibson, D. G.; Young, L.; Chuang, R. Y.; Venter, J. C.; Hutchison, C. A.; Smith, H. O.
We describe an isothermal, single-reaction method for assembling multiple overlapping DNA molecules by the concerted action of a 5? exonuclease, a DNA polymerase and a DNA ligase. First we recessed DNA fragments, yielding single-stranded DNA overhangs that specifically annealed, and then covalently joined them. This assembly method can be used to seamlessly construct synthetic and natural genes, genetic pathways and entire genomes, and could be a useful molecular engineering tool.
Keywords: DNA MOLECULES